Ultrasound characteristics of changes non-inflammatory origin in the knee joints of adolescents - Shevchenko, Natalya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
In order to study the state of articular structures, the knee joints of adolescents with complaints about persistent arthralgia and without any clinical signs of gonitis were examined with use of ultrasound. The article contains results of examination of 299 people (the basic group), 96 cases with signs of connective tissue dysplasia without joint syndrome (the comparison group) and 100 clinically healthy adolescents (the control group). The basic group revealed a lower altitude and a less degree of destruction of the articular cartilage, signs of an inflammatory process and irregular bone surfaces. Changes in the knee joint structure make it possible to believe that the morphological disturbances, observed in adolescents, agree with the concept of the formation of degenerative processes in adults.